Digital Game-Based Language Exposure: Indonesian University Students’ Perceptions of English Reading in Genshin Impact - Muhammad Danish Ridwan Abiyyu; Izzati Gemi Seinsiani (Jurnal Pendidikan Edutama, 2026)
This study investigated how language selection in Genshin Impact influenced Indonesian university students’ perceptions of English reading comprehension and explored the motivations behind their language choices. Employing a qualitative case study design supported by descriptive quantitative data, data were collected through screening questionnaires and semi-structured interviews, then analyzed using thematic analysis. The research involved 33 questionnaire respondents and 6 interview participants selected through purposive sampling. The findings revealed that the majority of participants (81.8%) perceived English-language gameplay as beneficial for vocabulary acquisition, reading speed, and exposure to contextual language use. However, English was also perceived as cognitively demanding due to complex narrative structures and fantasy terminology. Meanwhile, Indonesian was preferred for narrative comfort, emotional connection, and easier comprehension. Students’ language choices were strongly influenced by motivations related to self-improvement, authenticity, entertainment, localization quality, and social interaction. The study suggests that narratively rich video games can function as meaningful informal learning environments that support English reading development outside formal educational settings.